Joining the Conversation: Graduate Students’ Perceptions of Writing for Publication - Sarah M. Nielson; Tonette S. Rocco (Adult Education Research Conference, 2002)
The authors report on their qualitative study of eight students in a class on writing for publication and the nature of the writing process in academia. While the participants found value and purpose in writing and scholarly writing, they had great difficulty with criticism and using feedback in constructive ways.